The Evolution of Early Childhood Teacher Wellbeing Research (2020-2024): A Bibliometric Analysis of Global Trends - Esita, Zulaeni; Azis, Fatimah; Munirah, Munirah (PPSDP International Journal of Education, 2025)
This study conducts a bibliometric analysis to examine global research developments on teacher wellbeing in early childhood education (ECE) from 2020 to 2025. The growing recognition that teachers’ psychological, emotional, and professional wellbeing affects children’s learning outcomes underscores the need to systematically map this field. Drawing on data from Scopus, SciVal, and VOSviewer, a total of 151 documents were analyzed to evaluate research productivity, citation impact, collaboration patterns, and thematic evolution. The findings indicate a significant growth in publication output, accompanied by strong international collaboration and a Field-Weighted Citation Impact (FWCI) of 1.23, reflecting above-average global influence. Science mapping identified five major thematic clusters: (1) psychological dimensions of wellbeing, including burnout and mental health; (2) job demands–resources and institutional policy; (3) resilience and intervention studies in the post–COVID-19 context; (4) positive psychology and self-efficacy enhancement; and (5) links between teacher wellbeing and child development outcomes. Overall, the results highlight a paradigm shift from stress- and burnout-centered research toward strength-based, growth-oriented wellbeing models. Despite the dominance of high-income countries such as the United States, China, and Hong Kong, substantial research gaps persist in developing contexts. These findings underscore the need for context-sensitive, self-care–based, and digital wellbeing interventions to support sustainable ECE teacher wellbeing globally.